2012
DOI: 10.1038/bmt.2012.228
|View full text |Cite
|
Sign up to set email alerts
|

Chest health surveillance utility in the early detection of bronchiolitis obliterans syndrome in children after allo-SCT

Abstract: To prospectively assess whether periodic chest health surveillance is beneficial for the early detection of bronchiolitis obliterans syndrome (BOS) in children after allo-SCT. Children up to 18 years of age receiving allo-SCT from September 2009 to September 2011 were included. Surveillance consisted of the following: a 7-item respiratory system questionnaire of cough, wheeze and shortness of breath; focused physical examination; and pulmonary function test (PFT) conducted before SCT and at 1, 3, 6, 9, 12, 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Ways to improve diagnostic sensitivity and specificity for BOS after HSCT could thus be important for improving outcomes. Recent data have revealed that decline in PFT parameters was the best way to identify children at risk for BOS 27 and support prior publications in adults. 1 The importance of FEV1 in the characterization of the severity of BOS is long established.…”
Section: Discussionsupporting
confidence: 77%
“…Ways to improve diagnostic sensitivity and specificity for BOS after HSCT could thus be important for improving outcomes. Recent data have revealed that decline in PFT parameters was the best way to identify children at risk for BOS 27 and support prior publications in adults. 1 The importance of FEV1 in the characterization of the severity of BOS is long established.…”
Section: Discussionsupporting
confidence: 77%
“…The clinical equivalent, BO Syndrome (BOS), requires at least one distinctive extra‐pulmonary sign for cGvHD diagnosis, in addition to a forced expiratory volume in 1 sec (FEV 1 ) < 75%, FEV 1 /forced vital capacity (FVC)‐ratio < 0.7, residual volume (RV) > 120%, and signs of air‐trapping, bronchiectasis, or peribronchial thickening by high resolution computed tomography (HRCT), not attributable to infection . Typical symptoms of BO and BOS include cough, dyspnea, and wheezing, but patients may be relatively asymptomatic in the early stages …”
Section: Introductionmentioning
confidence: 99%
“…Reduction in PFTs is the mainstay for BOS diagnosis; however, a significant reduction occurs while the patient is completely asymptomatic, and by the time the diagnosis is made based on PFT reduction, significant lung damage has already occurred [29]. Furthermore, young children are uncooperative or unable to perform effective PFTs.…”
Section: Discussionmentioning
confidence: 94%